Karakteristik dan Model Bimbingan atau Pendidikan Islam Bagi ABK Tuna Wicara - Akhmad, Fandi; Ediansyah, Pemy; Fitriah, Januari; Farameida, Elsa; Purwanto, Joko (MASALIQ, 2021)
Education is an effort to improve the quality of human resources. Education can be obtained through formal or non-formal institutions. In formal education institutions there are regular classes and inclusive classes. Where in the class there are not only regular children but also some children with special needs. Children with special needs (ABK) are defined as individuals who have different characters from other individuals. In particular, children with special needs show physical, ability, and emotional characteristics that are lower or higher than regular children of their age imposed in society. Like children with special needs who are speech impaired. Children with special needs with disabilities are people who experience abnormalities both in terms of pronunciation (articulation). Thus, education is not only for regular children, but children with special needs are also entitled to a proper school. It is also intended that as Indonesian citizens who uphold the values of justice in Pancasila can be applied properly.